Does altered Ki67 expression in recurrent membranous basal cell adenoma point toward the need for reclassification? - Dhinakaran Paranchodi; Ashok Vikey; Jaya Joshi; Ramya Selvam; Neha Choudhary (Oral Oncology Reports)
The pathogenesis of membranous BCA recurrence remains unclear, with only a few cases reported. The current study focuses on a case that exhibits a high Ki-67 proliferative index, which raises questions about its impact on the prognosis and treatment plan. We have conducted a literature review to gain insight into the altered ki67 expression pattern in membranous BCA. We have also proposed a hypothesis that suggests recurrent membranous BCA cases with Ki67 levels between 5 % and 10 % signify an intermediate grade and warrant reclassification. More research is needed to confirm this hypothesis and understand the prognosis for this variant.